ANALISIS DIMENSI KUALITAS PELAYANAN DAN KEPUASAN PENGGUNA JASA GOJEK (Studi Kasus pada Mahasiswa Universitas Surakarta) - Trisnowati, Juni; Pujiani, Dewi; Susma, Devi (Universitas Slamet Riyadi, 2020)
This study aims to analyze the influence of service quality dimensions consisting of credibility, responsiveness, courtesy and security on Gojek service user satisfaction. This is motivated by the tendency of changing consumer behavior in using transportation services from conventional to online. And this requires companies to provide quality service in accordance with changes in consumer behavior. The population in this study were students of the University of Surakarta who used Gojek services. The population size in this study cannot be known with certainty. The sampling technique used was purposive sampling method, with a total sample size of 100. The data analysis techniques used included the coefficient of determination (R2), multiple linear regression, F test and t test. The results showed R2 of 0.529, this means that 52.90% of Gojek service user satisfaction is explained by the dimensions of service quality consisting of credibility, responsiveness, courtesy, and security, while the remaining 47.10% is explained by other variables. The results of multiple regression analysis obtained the equation Y = 0.305X1 + 0.224 X2 + 0.123 X3 +0.239 X4. The results of the F test show that the value of F count Ëƒ F table (28.821 Ëƒ 2.467) and significance